Kuat Tekan Beton Kubus Pasca Bakar Menggunakan Ultrasonic Pulse Velocity (Upv) Dan Compression Testing Machine (Ctm) - Wicaksono, Adhithiya; Suryanita, Reni; Sitompul, Iskandar Romey (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
High temperature changes may occur at the time of the fire. This can result in discoloration, cracking and loss of strength on concrete. Therefore, a test was conducted to identify the changes of concrete compressive strength. The concrete compressive strength was measured by using Ultrasonic Pulse Velocity (UPV) and Compression Testing Machine (CTM). The specimens used in this study was cube with the size of 150???? 150???? 150 mm. The specimen used consist of 18 cubes with the expected concrete compressive strength of 20, 25 and 30MPa. And then, the specimens were burned in a local brick furnance for about 30 minutes. The test results of post burn concrete, indicated that there was a decrease in the concrete compressive strength for all specimens. Based on the test results of post burn concrete using CTM and UPV, there was a significant difference. On UPV test using Mahure’s Equation compared with the results of CTM has a difference 7.3, 4.4 and 12.5 MPa. Whereas if the test using Nash't’s Equation compared with CTM has a difference 7.1, 4.7 and 8.6 MPa. Therefore, it can be concluded that to identify post burn concrete compressive strength usingCTM more accurate than UPV.Keywords: Compressive strength, concrete after burn, Ultrasonic Pulse Velocity (UPV), Compression Testing Machine (CTM).